1989
DOI: 10.2135/cropsci1989.0011183x002900050002x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Half‐Sib Family Selection for 2,4‐D Tolerance in Red Clover

Abstract: Low profit potential as well as environmental residue and toxicology concerns make it difficult for chemical companies to develop and register herbicides for forage crops. Selection of forages with tolerance to currently labeled herbicides may be an alternative. The objective of this research was to develop a 2,4‐D [(2,4‐di‐chlorophenoxy) acetic acid] tolerant red clover (Trifolium pratense L.) population, using recurrent half‐sib family selection. A 20 000 plant base population of equal parts of ‘Nolins’, ‘Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Both a greenhouse and a field experiment were conducted to evaluate the progress made from the initial four cycles of half‐sib family selection program conducted to increase levels of 2,4‐D tolerance in red clover. Methods for these experiments were described in Taylor et al (1989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both a greenhouse and a field experiment were conducted to evaluate the progress made from the initial four cycles of half‐sib family selection program conducted to increase levels of 2,4‐D tolerance in red clover. Methods for these experiments were described in Taylor et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…1 shows the process in a flow chart. These four selection cycles were conducted as part of a doctoral research project (Taylor et al, 1989). After this project, two additional cycles of recurrent phenotypic selection were conducted, but records of exact selection percentages in each cycle were not kept.…”
Section: Breeding Historymentioning
confidence: 99%
See 1 more Smart Citation
“…For some time, researchers have been attempting to incorporate resistance to 2,4-D into desirable plants that are normally sensitive either through selective breeding (Devine et al 1975;Munoz et al 2015;Taylor et al 1989) or biotechnology (Bayley et al 1992;Charles et al 2007;Wright et al 2010). The objectives were generally to allow use of 2,4-D on the crop of interest or incorporate greater tolerance to low rates occurring from off-target movement.…”
Section: 4-d-resistance Traitsmentioning
confidence: 99%
“…Primary methods for breeding red clover have been either recurrent mass selection or recurrent half‐sib selection (Taylor and Quesenberry, 1996), and these methods are easily applied to both selection for dormancy response (Quesenberry et al, 1993) and RKN response (Quesenberry et al, 1989). It has also shown that these methods can be successfully used for selection for 2,4‐D tolerance (Taylor et al, 1989) and for plant regeneration from callus tissue culture (Quesenberry and Smith, 1993; Quesenberry et al, 1996).…”
mentioning
confidence: 99%